Geochemical Systematics of High Arctic Large Igneous Province Continental Tholeiites from Canada—Evidence for Progressive Crustal Contamination in the Plumbing System. (9th June 2021) - Bédard, Jean H; Saumur, Benoit Michel; Tegner, Christian; Troll, Valentin R; Deegan, Frances M; Evenchick, Carol A; Grasby, Stephen E; Dewing, Keith
Abstract: Cretaceous High Arctic large igneous province (HALIP) sub-alkaline magmatic rocks in Canada are mostly evolved (MgO 2–7 wt%), sparsely plagioclase + clinopyroxene ± olivine-phyric tholeiitic basalts. There were two main HALIP continental flood basalt (CFB) eruption episodes: 135–120 Ma (Isachsen Fm.) and 105–90 Ma (Strand Fiord Fm.), both associated with cogenetic doleritic sills and dykes. Building on a large modern database, 16 HALIP tholeiite types are defined and grouped into genetic series using Ce vs Sm/YbNMORB distributions. Comparison with model melting curves implies that higher-Sm/Yb HALIP basalt types record low-degree melting of garnet-bearing mantle sources. More voluminous intermediate- and low-Sm/Yb HALIP basalt types separated from the mantle at shallower levels after further extensive melting in the spinel-peridotite field. Within a given Sm/Yb range, increases in incompatible elements such as Ce are coupled with progressive clockwise rotation of normalized incompatible trace element profiles. Trace element modeling implies this cannot be due to closed-system fractional crystallization but requires progressive and ubiquitous incorporation of a component resembling continental crust. The fractionation models imply that low-Sm/Yb HALIP basalts (∼7 wt% MgO) initially crystallized olivine gabbro assemblages, with lower-MgO basalts successively crystallizing gabbro and ilmenite-gabbro assemblages. In contrast, higher-Sm/Yb basalts fractionated more clinopyroxene and ilmenite, but extensive plagioclase fractionation is still required to explain developing negative Sr–Eu anomalies. Back-fractionation models require about 40 % addition of olivine to bring the most primitive HALIP basalts (∼7 % MgO) into equilibrium with Fo89 mantle. Inverse fractionation–assimilation modeling shrinks the CFB signature, making decontaminated model parental melts more similar to enriched mid-ocean ridge basalt. The progressive increase of the contamination signature within each HALIP tholeiitic differentiation series is not consistent with models involving derivation of HALIP basalts from a mantle source previously enriched by subduction. Strong interaction of basalt with Sverdrup Basin sedimentary rocks may cause localized over-enrichment in K–Rb–Th–U, but cannot explain strong Ba enrichment in the absence of concomitant K–Rb–Th–U enrichment. The localized Ba enrichment could reflect either a Ba-rich lithospheric mantle component that is strongly manifested in the coeval HALIP alkaline suites, or syn- to post-emplacement fluid-mediated transfer from Ba-rich host rocks.